Both IL-1β and TNF-α Regulate NGAL Expression in Polymorphonuclear Granulocytes of Chronic Hemodialysis Patients - Adriana Arena; Giovanna Stassi; Daniela Iannello; Domenica Gazzara; Maria Calapai; Carlo Bisignano; Davide Bolignano; Antonio Lacquaniti; Michele Buemi (Mediators of Inflammation)
Background. NGAL is involved in modulation of the inflammatory response and is found in the sera of uremic patients. We investigated whether hemodiafiltration (HDF) could influence the ability of polymorphonuclear granulocytes (PMGs) to release NGAL. The involvement of interleukin- (IL-)1β and tumor necrosis factor- (TNF-)α on NGAL release was evaluated. Methods. We studied end-stage renal disease (ESRD) patients at the start of dialysis (Pre-HDF) and at the end of treatment (Post-HDF) and 18 healthy subjects (HSs). Peripheral venous blood was taken from HDF patients at the start of dialysis and at the end of treatment. Results. PMGs obtained from ESRD patients were hyporesponsive to LPS treatment, with respect to PMG from HS. IL-1β and TNF-α produced by PMG from post-HDF patients were higher than those obtained by PMG from pre-HDF. Neutralization of IL-1β, but not of TNF-α, determined a clear-cut production of NGAL in PMG from healthy donors. On the contrary, specific induction of NGAL in PMG from uremic patients was dependent on the presence in supernatants of IL-1β and TNF-α. Conclusion. Our data demonstrate that in PMG from healthy subjects, NGAL production was supported solely by IL-1β, whereas in PMG from HDF patients, NGAL production was supported by IL-1β, TNF-α.